Algebra 1

1.18x^2 + 6 + 4x - 15x^2 - 4 + 13x
2. 2x^2 + 8 - 4x + 3x - 6x^2 + 7

  1. 👍
  2. 👎
  3. 👁
  1. 18x^2 + 6 + 4x - 15x^2 - 4 + 13x

    3x^2 + 17x + 2

    Now you try the second problem.

    1. 👍
    2. 👎
    👤
    Ms. Sue

Respond to this Question

First Name

Your Response

Similar Questions

  1. math ~dont know all but check some~ pls help!!!

    1. Draw a model to represent the polynomial x2 + 2x + 4. (1 point) 1 big square, 1 tall rectangle, 4 little sqaures 1 big square, 2 tall rectangles, 4 little sqaures in the shape of an "L" 2 big sqaures, 4 little squares none of

  2. Algebra 2 H

    Find x-values if any at which the function f(x)=13x^2-15x-15 is not continuous. Which of the discontinuities are removable? THANKS YOU!!

  3. Math Check Answers

    Write a rule for the function represented by the table. x y 0 13 1 28 2 43 3 58 y= 15 + 13x y= 14 + 12x y= 13 + 15x** y= 12 + 14x Which function rule would help you find the values in the table? j k 2 -12 4 -24 6 -36 8 -48 k= -12j

  4. Math

    9x^2+16y^2-18x+64y-71=0 find the coordinates of the center, the foci, and the vertices of this ellipse. 9x^2+16y^2-18x+64y-71=0 9x^2-18x+16y^2+64y=71 9(x^2-2x)+16(y^2+4y)=71 9(x^2-2x+1)+16(y^2+4y+4)=71

  1. Geometry

    Angle JKL is congruent to angle MNP, KL= 21x - 2, NP = 20x, LJ = 15x, PM = 13x + 4. Find LJ. I don't understand how to do it! Please, help! :)

  2. Algebra

    Simplify (-24x^3+18x+6)/(6x+3) -4x^2+2x-2 4x^2-2x-2 4x^2+2-2 -4x^2+2x+2 I need a bit help on this. I don't know how to do it. I think the first step is divide 18x+6 with 6x+3 and 6x+3 divide by 6x+3. Am I on the right track?

  3. Math

    f(x)=13x^2 -15x-14 g(x)=15x^3+14x^2-15x+12 find f(3) × f(10) + f(-7) × g(9)

  4. geometry

    What type of quadrilateral is formed by connecting the points (0,0), (3x,b), (18x,b), and (15x,0)? Explain. How would I solve this?

  1. math

    Multiplying and Dividing Rational Expressions: 2) x^2-8x+7/x^2+6x-7 = (x-7)/(x+7) 3) x^2-5x+6/x+4 times 3x+12/x-2 =3(x-3) 4)2x-3/5x+1 divided by 6x^2-13x+6/15x^2-7x-2=1 5) x^3-9x/x^2+11x+24 times x^2+7x-8/x^2-4x+3=

  2. math

    Multiplying and Dividing Rational Expressions: 2) x^2-8x+7/x^2+6x-7 = (x-7)/(x+7) 3) x^2-5x+6/x+4 times 3x+12/x-2 =3(x-3) 4)2x-3/5x+1 divided by 6x^2-13x+6/15x^2-7x-2=1 5) x^3-9x/x^2+11x+24 times x^2+7x-8/x^2-4x+3=

  3. Algebra 2

    I had to solve this quadratic equation using the complete the square method. Did I do it correctly? The problem is 3x^2+18x+10= 0 (3x^2+18x+10)/3= 0/3 = x^2+6x+(10/3)=0 x^2+6x+(10/3)-(10/3)=0-(10/3) =x^2+6x= (-10/3( x^2+6x

  4. Math

    William solves the equation 5(3x-2)=15x-2. How many solutions does he find? A.0 solutions B.1 solution C.2 solutions D.Infinitely many solutions I'm only up to making it to: 15x-10= 15x-2 I was also wondering if I did anything

You can view more similar questions or ask a new question.